Control Bandwidth Promotion of Adaptive Fiber-Optics Collimator and Its Application in Coherent Beam Combination - Guan Huang; Chao Geng; Feng Li; Jiaying Liu; Xinyang Li (IEEE Photonics Journal, 2018)
Adaptive fiber-optics collimator (AFOC) plays an important role in the coherent beam combining (CBC) systems. To improve the control bandwidth, the frequency characteristics of AFOC are measured, and an accurate transfer function model is established. Through the analysis of this model, we find that the resonance and the inherent response delay are the main limiting factors. To solve these two problems, an active resonance suppression method based on biquad filters and an improved control algorithm named precise-delayed stochastic parallel gradient descent (PD-SPGD) is proposed. The resonance suppression experiment shows that when the frequency is within 10 kHz, the fluctuation in the AFOC's amplitude-frequency characteristic is suppressed within ±3 dB by the biquad filters, and the phase-frequency characteristic is compensated to be similar to a pure delay element (with inherent response delay of about 88 μs). The two-channel CBC experiment shows that the algorithm's iteration rate increased from 1.6 to 6 kHz and the convergence time decreased from 5.63 to 1.83 ms when the biquad filters and PD-SPGD are used together, which indicate that the AFOC's actual control bandwidth is about 3.1 times higher than before.